Influence of Maturity Status on the Reliability of the 3-Point Line Curve Sprint Test in Young Basketball Players - Pedro Muñoz-Fole; Andrés Baena-Raya; Ezequiel Rey; Manuel Giráldez-García; Alexis Padrón-Cabo (Applied Sciences)
This study was designed to evaluate the influence of maturity status in the inter- and intra-session reliability of curvilinear sprinting (CS) and compare the reliability of the half-CS trials with the complete CS trials. Forty-two youth basketball players from an elite academy (13.1 ± 1.7 years; 166.7 ± 16.2 cm; 57.2 ± 17.0 kg) performed two sessions of three CS trials each on both right and left sides with seven days of separation between sessions. The predicted peak height velocity (PHV) was used to establish players’ maturity status (pre-PHV, n = 14; mid-PHV, n = 14; post-PHV = 13). Mid- and post-PHV groups showed a high relative (interclass correlation coefficient [ICC] ≥ 0.75) and absolute (coefficient of variation [CV] < 5%) reliability inter- and intra-session, and pre-PHV showed high relative and absolute reliability in the left trials and in the CS right trial, but moderate (ICC = 0.73) relative reliability in the half-CS right side. Based on these findings, it is recommended that practitioners consider players’ maturity status to ensure accurate and reliable assessments of CS performance.